Flowing through Virtual Animated Worlds – Perceptions of the Metaverse - Cruz, M.; Oliveira, A.; Pinheiro, A. (Eurasian Conference on Frontiers of Computer Science and Information Technology (FCSIT 2022), 2022)
In our daily lives in modern societies, our reality and the perceptions and perspectives that we have about it, are constantly being transformed or shaped by technology. Different types of technology influence our representations, whether physical, social, or virtual. So, we must learn to live along with it. How far and how deep can we go? How aware are we of the time we spend in virtual immersion, and of the significance of the metaverse? To find out possible answers to these questioning, we need to consider a previous and critical question: How do we perceive the metaverse? This is our starting point – or research question. (To go further, we should also research about how we are linked (or submerged) in the metaverse.) The aim of the present study is to explore how the metaverse is present in our everyday – considering an adult population - and what are our perceptions about it. It consists on a documental analysis – or meta-analysis – of 15 of the most relevant scientific papers (according to some inclusion criteria), published in the last 2 years, using the Iramuteq and WordCloud MonkeyLearn Software to determine and model the main themes and associated concepts with the metaverse, linked to virtual reality, animation or gaming – this is important in order to establish possible associations between these topics, and analyze, in a broader way, the metaverse. Initial results suggest that people use and consider virtual reality - and the metaverse - as a means of socializing and communicating, inseparable from their daily lives, whether at a playful, learning or even professional level. This exploratory study gave us important findings about the perceptions of the metaverse and clues to verify links between it and the associated themes. Our results will not just help us understand which topics can be more deeply investigated, but also be useful for us to verify the most relevant research items to be considered in a PhD project in preparation.